Minimal Solutions of Fuzzy Relation Inequalities With Addition-Min Composition and Their Applications - Li, Meng; Wang, Xue-ping (IEEE transactions on fuzzy systems, 2023)
This article deals with the set of minimal solutions for fuzzy relation inequalities with addition-min composition. We first show a necessary and sufficient condition for a solution of the fuzzy relation inequalities being a minimal one, then we propose an algorithm to find all minimal solutions of the fuzzy relation inequalities. Finally, we use all minimal solutions of the fuzzy relation inequalities to solve the related optimization problems, which will be illustrated by a series of numeral examples.